Abdominal midline wound closure with small bites versus large bites: a randomized comparative trial - Sharma, Rajat; Kaur, Amitpal; Sharma, Mohit; Singh, Karaninder; Singh, Neeti Rajan (International Surgery Journal, 2020)
Background: The optimal strategy of abdominal wall closure after midline laparotomy has remained an issue of ongoing debate to minimize incidence of incisional hernia which occurs in 10 to 23% cases postoperatively. The main objective of the study was to evaluate the efficacy of small bites versus large bites suture technique in reduction of incidence of the complications like pain, wound infection, wound dehiscence, seroma formation and incisional hernia by using polydioxanone no.1. Methods: The present study was conducted on 100 patients undergoing elective surgery who were randomly allocated into group A and B. Group A were the patients in which midline abdominal wound closure was done with small bites and group B were the patients in which midline abdominal wound closure was done with large bites. Then the patients were followed up for 6 months to observe any complications. Results: A mean additional closure time of 9 minutes was seen with the small bites technique. The mean suture length was more in small bites group as compared to large bites technique. There was no difference in the visual analog scale score between the two groups. No significant difference was seen in the incidence of major and minor wound infection postoperatively in both the groups. Small bites technique reduced the incidence of suture sinus and incisional hernia compared to conventional large bites technique. Conclusions: It can be concluded that the small bites suture technique is more effective than the traditional large bites technique for prevention of all post-operative complications.